ANALYSIS OF STABILITY OF THE CLASSIFYING RULES PROCESSINGS OF TEXT INFORMATION - M. A. Silbergleit; A. S. Ryzhankova (Системный анализ и прикладная информатика, 2015)
In article is described the analysis of stability of classification functions when processing text information on the basis of application of various methods of transformation of data. That the educational text in this research is considered as formal and logical education, as its main characteristics 14 statistical parameters making factorial space of objects of research are determined. The analysis of stability of the classifying rules is carried out on the basis of the analysis calculated for each of methods of transformation of coefficients of a variation.